THE CONCEPT OF SUSTAINABLE EDUCATION AND THE IMPORTANCE OF DIGITAL TRANSFORMATION (World Bulletin of Education and Learning, 2025)
Digital transformation is an important part of the strategic development of an enterprise in the modern world, implying a change in approaches to labor, culture and technology. The article considers the issue of implementing digital strategies as an integral step towards sustainable development. To implement a successful digital transformation, it is important to analyze the company's business model, which will help identify opportunities for optimizing business processes, as well as develop effective mechanisms for managing digital transformation.
Keywords: Sustainable education, sustainable development, digital transformation, digital strategy, digital economy, digital technology.